2011
DOI: 10.1186/1297-9716-42-53
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of transmission parameters for bluetongue virus serotype 8 in Western Europe in 2006

Abstract: The recent bluetongue virus serotype 8 (BTV-8) epidemic in Western Europe struck hard. Controlling the infection was difficult and a good and safe vaccine was not available until the spring of 2008. Little was known regarding BTV transmission in Western Europe or the efficacy of control measures. Quantitative details on transmission are essential to assess the potential and efficacy of such measures.To quantify virus transmission between herds, a temporal and a spatio-temporal analysis were applied to data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 24 publications
2
79
0
Order By: Relevance
“…The role of animal transportation in the dissemination of BTV-8 in northwest Europe may have been significant [44].…”
Section: (D) Further Consideration Of the Extrinsic Incubation Periodmentioning
confidence: 99%
“…The role of animal transportation in the dissemination of BTV-8 in northwest Europe may have been significant [44].…”
Section: (D) Further Consideration Of the Extrinsic Incubation Periodmentioning
confidence: 99%
“…Some of these methods are based on data from surveillance and monitoring programmes. For example, [9] estimated between herds for the Netherlands. Furthermore, a theoretical study on using a deterministic epidemic model was introduced by [10] to investigate the seasonal spread of BTV over several years and to evaluate the effectiveness of vaccination strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The virus overwintered and spread over most of Europe causing massive losses to the livestock industries of several countries over a number of years [29], [30]. Phylogenetic analyses showed that the northern European strain of BTV-8 is most closely related to a strain from Central Africa [31], although the route of introduction has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%